P196 A Local Domiciliary Non-invasive Ventilation (NIV) Service Reduces Length of Hospital Stay for Patients Unable to Wean From NIV. (12th November 2015) - Lane, A; Harlow, S; Murray, P
Abstract : Background: NIV is a clinically proven treatment for acute hypercapnic respiratory failure. 1 Most patients are fully weaned from NIV before discharge from hospital but some with chronic ventilatory failure require long term NIV at home. Historically, these patients would need to wait for inpatient transfer to a tertiary centre for NIV titration. Due to the high demand for tertiary centre beds, this could take days to weeks. By this time, patients would frequently be optimised and stable on domiciliary NIV settings and only require transfer for equipment issue. A local domiciliary NIV service was commissioned in April 2012 to provide an integrated secondary care and community service closer to home and to reduce delayed discharge. Method: Data were collected prospectively from 83 consecutive patients between October 2006 and May 2014 (395.6 weeks) from patients on a respiratory ward, unable to fully wean and requiring domiciliary NIV on discharge. Results: See Table 1 . Discussion: Length of stay was reduced by an average of 4 days after the local domiciliary NIV service was initiated. Although this difference did not reach statistical significance it is certainly clinically significant, with huge pressure on clinicians to discharge patients in a timely manner. By managing the majority of these patients locally, it is hoped that the resources of the tertiary centres would be freed up to accept the very complex cases that still require tertiary centre input. Conclusion: The provision of a local Domiciliary NIV service reduces length of stay by reducing waiting times for inpatient transfer to tertiary centres. Reference: 1 Royal College of Physicians, British Thoracic Society, Intensive Care Society. Chronic obstructive pulmonary disease: non-invasive ventilation with bi-phasic positive airways pressure in the management of patients with acute type 2 respiratory failure . Concise Guidance to Good Practice series, No 11. London: RCP, 2008